STRUCTURE OF INCIDENCE IN VERY PREMATURE CHILDREN - Yuldasheva, Гулноз; Rustamov , Бахтиёр (International Journal of Scientific Pediatrics, 2024)
This review presents the results of an analysis of the birth of premature newborns at 22-32 weeks with extremely low birth weight during 2022-2023. It has been established that in 2022, 2.8% of the total number of births are premature. Of these, 0.8% are premature infants with extremely low body(500,0-999,0g), weight (ENMT), 2.0% are children with very low body (1000,0-1499,0g) weight (ONMT), respectively 0.9% and 1.8% in 2023. Preterm birth mainly occurs at 29-30 weeks (44%). The main diseases of the neonatal period in deeply premature newborns are: respiratory disorders, intrauterine pneumonia, central nervous system lesions, more often of ischemic-hypoxic genesis, congenital malformations, as a result of prolonged influence of pathological factors on the fetus. The purpose of the study: To analyze the incidence rates and its structure in deeply premature infants with extremely low body weight in 2022-2023. Materials and methods of research. 382 premature newborns with a gestation period from 22 to 36 weeks were examined, which comprised 2 groups: 1st - 122 extremely low birth weight (ENMT) newborns weighing 535.0–975.0g and 2nd - 260 premature infants with very low birth weight (ONMT) with a weight of 1011.0-1478.0g. The average gestational age (GG) in group 1 was 27.1±1.4 weeks, in group 2 -32.4±1.5 weeks. The features of the ante and intranatal periods, the results of clinical observation, and data from paraclinical examinations were studied. The results and their discussion. The morbidity structure of deeply premature infants in the maternity hospital was studied using the example of 2023. Congenital pneumonia is the main pathology of respiratory disorders (42.1%). It should be noted that children with ENMT were 1.6 times more likely to have pneumonia (60.4%) than children with ONMT (33.9%). Ante and intrapartum periods are often complicated by intrauterine hypoxia and asphyxia during childbirth (28.4%). Hypoxia is manifested in children with ENMT and ONMT at birth with the same frequency - 22.8% and 29.5% (p>0.05). Conclusion. Respiratory disorders prevail in the structure of diseases of premature infants — 82.4% of deeply premature infants as a result of morphofunctional immaturity of lung tissue and surfactant deficiency, intrauterine infection significantly increases the incidence rate (51.2%).